Illustration of bounded ambiguity. I, The 'feedback culture' of a management consultancy firm - Alvesson, Mats, 1956- (SAGE knowledge. Cases., 2016)
This case study presents an assessment of a human resource management system in a large management consultancy firm. Despite flaws in the system, it is largely viewed as an identity resource and a factor of image management. There is an ambiguity between people's individual experiences of human resource management within the firm and the functions of the overall system.